Scientific Insights and Technological Advances in Gluten Free Products Development - Papageorgiou, Maria; Varzakas, Theodoros (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue addresses both new scientific insights and technological advances of gluten-free product development exploring alternative ingredients for the development of gluten-free products aiming to mimic the unique viscoelastic properties of gluten as a gas retention ingredient during fermentation, water binding and enabler of starch gelatinization on baking, and a bread flavor enhancer via gluten-related proteases.